Improving Patient Education: Effective Ways to Develop and Deliver Information about Health-Related Behaviors - Christopher AhnAllen; DeAnna Mori (Association of American Medical Colleges, 2015)
Abstract This educational tool kit has been developed for health professional learners to provide instruction on patient education practices in health care as well as to engage learners in designing patient education tools. Patient education refers to a range of different methods (e.g., teaching, counseling, behavioral modification) that have the goal of improving the knowledge and health behaviors of the patient. By the end of this workshop, learners will be able to describe the important components of developing and delivering patient education, create an educational tool, and obtain information about funding opportunities that support patient education development. The module includes a faculty guide, a small-group activity, a supplemental reading list, and other associated handouts. In 2014, this educational workshop was conducted at a psychology faculty and trainee education day at an academic medical center. A total of 45 minutes was allocated for this workshop at that time, and priority was given to providing education about patient education and reviewing tips for developing materials. The Tips for Developing Materials Handout and Funding Resources Handout were disseminated. Attendees provided feedback indicating that overall, the educational workshop was well received (ratings were conducted using a 1-5 Likert scale; 1 = Strongly Disagree, 2 = Disagree, 3 = Neutral, 4 = Agree, 5 = Strongly Agree). Attendees found the content and objectives to be appropriate and relevant to their practice (M = 4.75), were able to identify the important components of developing and delivering patient education (M = 4.25), believed they could create an educational tool (M = 4.25), and could identify funding opportunities to support patient education development (M = 4.25). There is potential to expand this workshop by including follow-up sessions to allow learners to develop their patient education products further. With additional time, they could also solicit feedback from others in their clinical area of expertise and from patient populations and review previously produced materials in the community.